Overweight and Obesity and its Associated Factors Among Office Staff at a Higher Education Institute in Malaysia. (Bangladesh Journal of Medical Science, 2023)
Introduction: Overweight and obesity caused by excess body fat accumulation is a leading public health problem globally. The objective of this study was to investigate the overweight and obesity prevalence and its accompanying factors among educational office staff in Kuantan, Malaysia.Materials and Methods: A cross-sectional study was conducted among the staff of Widad University College (WUC) and Widad College (WC) using a self-administered validated questionnaire. Socio-demographic characteristics of the participants and obesity-related health information such as body mass index (BMI), smoking, alcoholics, physical activities and blood pressure status were obtained. The BMI was determined considering the participants weight in kilograms (kg) divided by the square of height in meters (kg/m2). Correlating the BMI with sociodemographic and health-related factors, the participants were characterized as underweight, normal, overweight and obese and presented as mean, frequency and percentage distribution. A p-value of